Evaluation of Technical Shrinkage of Express Extension PL 03 and LW 09 at PLN Lhoksukon Using ETAP Software - Raihan Putri; Dheo Pratama; Arnawan Hasibuan; Muchlis Abdul Muthalib; Nanda Sitti Nurfebruary (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
The electricity distribution system generally starts from the generation, transmission, and distribution systems. In the distribution system, there are two channels, namely primary distribution with a voltage value of 20 kV and secondary distribution with a voltage of 220/380 V. Distributing electrical energy often experiences problems, one of which is the occurrence of energy losses during the distribution of electrical power to customers. Energy losses are energy losses due to technical and non-technical factors. This study evaluates energy losses due to technical factors in the express extension PL 03 and LW 09 PT PLN (Persero) ULP Lhoksukon. The method used to assess energy losses due to technThe calculation results show that theological factors with ETAP software simulations and more detailed technical shrinkage calculations, namely by calculating conductor and transformer shrinkage on the repeater. From the results of the ETAP simulation, it is obtained that the voltage losses of the PL 03 and LW 09 Lhoksukon ULPs still meet the standards according to SPLN 1: 1995 for a voltage of 20 kV where the limits set are +5% maximum and -10% minimum of the system voltage. The drop Voltage of PL 03 Extension is 7.6%, and LW 09 Extension is 8.25% of the nominal voltage of 20 kV. From the calculation results, of Drop Voltage of the PL 03 Repeater is 5.5%, and the LW 09 Repeater is 8.5% of the nominal voltage of 20 kV.